The Colonial Project of Gender (and Everything Else) - Sandy O’Sullivan (Genealogy, 2021)
The gender binary, like many colonial acts, remains trapped within socio-religious ideals of colonisation that then frame ongoing relationships and restrict the existence of Indigenous peoples. In this article, the colonial project of denying difference in gender and gender diversity within Indigenous peoples is explored as a complex erasure casting aside every aspect of identity and replacing it with a simulacrum of the coloniser. In examining these erasures, this article explores how diverse Indigenous gender presentations remain incomprehensible to the colonial mind, and how reinstatements of kinship and truth in representation fundamentally supports First Nations’ agency by challenging colonial reductions. This article focuses on why these colonial practices were deemed necessary at the time of invasion, and how they continue to be forcefully applied in managing Indigenous peoples into a colonial structure of family, gender, and everything else.